Structure and reactivity of a siderophore-interacting protein from the marine bacterium Shewanella reveals unanticipated functional versatility - Trindade, Inês B. (2019)
This work was supported by the European Union’s Horizon 2020 research and innovation program under Grant 810856, National Funds Grant ERA-MBT/ 0003/2014, Ph.D. fellowship PD/BD/135187/2017 (to I. B. T.), and postdoctoral fellowships SFRH/BPD/94050/2013 and SFRH/BPD/93164/2013 (to E. M. and B. F. M.), through the FCT-Fundação para a Ciência e Tecnologia. The authors declare that they have no conflicts of interest with the contents of this article. Acknowledgments—We thank Isabel Pacheco for help in the purification of SfSIP and Dr. Américo Duarte for providing ferredoxin. We also thank all members of the Inorganic Biochemistry and NMR Laboratory for discussions and comments and feedback regarding the preparation of the manuscript. The NMR experiments were performed at CERMAX (Centro de Ressonância Magnetica António Xavier) and was financially supported by Project LISBOA-01-0145-FEDER-007660 (Microbiologia Molecular, Estrutural e Celular) funded by FEDER funds through COMPETE2020-Programa Opera-cional Competitividade e Internacionalização (POCI), the European Community’s Seventh Framework Program (FP7/2007–2013)) under Grant Agreement 283570 (BioStruct-X). Beamtime at I04 at the Diamond Light Source and assistance from the beamline staff during the synchrotron data collections are gratefully acknowledged.